When Clusters become Networks - Sandra Phlippen; Bert van der Knaap (Tinbergen Institute, 2007)
Policy makers spend large amounts of public resources on the foundation of science parks and other forms of geographically clustered business activities, in order to stimulate regional innovation. Underlying the relation between clusters and innovation is the assumption that co-located firms engaged in innovative activities benefit from knowledge that diffuses locally. In order to access this knowledge, firms are often required to form more- or less formal relations with co-located firms. Empirical evidence shows however that besides some success cases like Silicon Valley and the Emilia- Romagna region where firms collaborate intensively, many regional clusters are mere co-locations of firms. To enhance our understanding of why some clusters become networks of strategic collaboration and others don't, we study link formation within European biopharmaceutical clusters. More specifically we look at the effect of cluster characteristics such as number of start-up firms, established firms or academic institutions, or the nature of the collaborations on the probability of local link formation
Keywords: R11; R12; R58; D83; D85; 330; regional clusters; networks; local & global linkages; pharmaceutical industry; Regionales Cluster; Unternehmensnetzwerk; Strategische Allianz; Pharmazeutische Industrie; Europa